Firm's efficiency and foreign ownership: evidence from Turin automotive cluster. (1st January 2012) - Manello, Alessandro
During the last decade many contribution underline the importance of multinationals presence arguing their higher productivity. This paper presents a non-parametric estimate of efficiency levels and productivity trends of firms operating in the automotive sector near Turin. The obtained results are analysed using one of the most modern and robust semi-parametric technique. This allows to draw a more precise picture of the relation between ownership and productivity, cleaning for misleading individual characteristics. Large automotive multinationals appear to be less efficient in combining inputs to obtain outputs and they are also less able to improve productivity during the crisis. No evidence is found for small and medium firms owned by a foreign subject.